Psychiatry at a glance - Katona, C. L. E. [ (Cornelius L. E.)] , 1954-; Cooper, Claudia; Robertson, Mary M. (At a glance series, 2012)
Provides all the information required, including practice questions, for the written Psychiatry exams Helps develop practical history taking and examination skills and provides sample OSCEs Includes two new chapters on mental health capacity, and Australian and New Zealand mental health legislation Now supported by a companion website